The Emotional Experience of Learning and Teaching. - Osborne, Elsie (Karnac Books, 1993)
The authors - who are experienced teachers and analysts - examine the ways in which Kleinian and psychoanalytic ideas can be put to work in the classroom. The role of phantasy in the student-teacher relationship receives detailed attention.